FATIGUE LIFE PREDICTION AND EXPERIMENTAL STUDY OF ALUMINUM ALLOY WHEEL HUB CONSIDERING DAMAGE ACCUMULATION (MT) - WANG ZhaoHua; WU FengHe; LIU JiaLiang; LIAN Hui (Jixie qiangdu)
Aiming at the problem of fatigue life prediction of aluminum alloy wheel hub, a fatigue life prediction model considering damage accumulation is proposed and tested. The Finite Element Models of a wheel hub under bending fatigue test and radial fatigue test are established, and the main failure positions are studied by simulation analysis. The S-N curves of material and part are established by using the nominal stress method, and the average stress of the asymmetric cyclic load borne by the wheel hub is corrected by using the Morrow line. Considering the rotation process of the wheel hub, a theoretical model for predicting the fatigue life is constructed by using the linear cumulative damage theory. Taking an aluminum alloy wheel hub as an example, the life calculated by the theoretical model is 448.2 thousands revolutions. Compared with the fatigue life of 473.3 thousands revolutions given by the bending fatigue test, the error is about 5.6%, which verifies the effectiveness of the fatigue life prediction theoretical model.